2016
DOI: 10.1093/conphys/cow060
|View full text |Cite
|
Sign up to set email alerts
|

Physical condition and stress levels during early development reflect feeding rates and predict pre- and post-fledging survival in a nearshore seabird

Abstract: Snapshot nestling health measures can reveal reproductive effects of environmental stress while minimizing handling, disturbance and researcher effort. We tested two short-term measurements, body condition and feather corticosterone, as predictors of brown pelican nestling survival. Both measurements predicted nestling survival to fledge, and feather corticosterone also predicted post-fledging survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 69 publications
2
13
0
Order By: Relevance
“…We did not find a significant relationship between colony size and either of the nestling condition metrics we tested (body condition or feather corticosterone). We have previously determined that both feather corticosterone and body condition are effective predictors of chick survival in this system (Lamb et al., ), so we can extrapolate from our results that the reproductive rates of pelicans do not decline with colony size. This result contradicts several previous studies suggesting a relationship between chick condition and colony size (e.g., Cairns, ; Gaston et al., ; Hunt et al., ); however, several other studies have failed to find a correlation (Ainley et al., ; Brown & Brown, ; Gaston et al., ).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…We did not find a significant relationship between colony size and either of the nestling condition metrics we tested (body condition or feather corticosterone). We have previously determined that both feather corticosterone and body condition are effective predictors of chick survival in this system (Lamb et al., ), so we can extrapolate from our results that the reproductive rates of pelicans do not decline with colony size. This result contradicts several previous studies suggesting a relationship between chick condition and colony size (e.g., Cairns, ; Gaston et al., ; Hunt et al., ); however, several other studies have failed to find a correlation (Ainley et al., ; Brown & Brown, ; Gaston et al., ).…”
Section: Discussionsupporting
confidence: 56%
“…Briefly, we removed the feather rachis, cut each feather into small (<0.5 mm) segments, extracted corticosterone in three successive methanol washes, reconstituted samples in buffer, and measured corticosterone concentrations via radioimmunoassay (MP Biomedicals, California, USA). Complete details of corticosterone analysis are described in Lamb, O'Reilly, and Jodice ().…”
Section: Methodsmentioning
confidence: 99%
“…After this point, nestlings become flight-capable and may leave the breeding colony (Shields 2014), and although adults may continue to visit the colony, they generally cease to feed nestlings after 60 days of age (Montgomery and Martínez 1984). Our own observations indicate that mortality of nestlings older than 8 weeks is extremely rare, making 60 days an appropriate cutoff for determining that a nest has successfully fledged young (Lamb 2016). For pelicans that re-nested following capture, we interpreted the start of attendance at the new site as the beginning of incubation and used a 90-day cutoff for successful breeding, incorporating 30 days of incubation (Shields 2014) in addition to the 60-day fledging period.…”
Section: Nesting Successmentioning
confidence: 89%
“…Nestlings were color-banded at 3-4 weeks of age to ensure that they could be followed after leaving the nest site. For full details of nest productivity monitoring methods and results, see Lamb (2016) and Lamb et al (in review).…”
Section: Nesting Successmentioning
confidence: 99%
“…The weak condition of urban birds may be also linked to the nutritional constraints that they suffer during early-life, which could negatively affect body condition in adulthood (Bókony et al, 2010;Seress et al, 2012), even if the restriction diminish at later life stages (Liker et al, 2008). Body condition, especially during development, is often positively correlated with pre-and post-fledgling survival rates (Lamb et al, 2016); consequently, poor condition is often observed in a declining population such as urban House Sparrows (Dulisz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%